Effects of Reactive Neuromuscular Training on Forward Head Posture among Higher Learning Institution (Academician & Non-Academician) Population - Mahendran Jayaraman,; Karthikeyan Jayabalan,; Yu Chye Wah,; Theingi Maung Maung,; Siva Sangary Murthy, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Reactive Neuromuscular training (RNT) activities are designed to restore functional stability on the joints and to enhance motor control skills, which can be defined as awareness of posture, movement, and changes in equilibrium and the knowledge of position, weight, and resistance of objects in relation to the body. Posture has been very important in preserving human balance. Awkward posture in various activities contributes to the increased risks of developing musculoskeletal disorders. Maintaining an upright sitting and standing posture is thus often suggested, especially nowadays when people spend longer periods in the sitting posture for occupational or leisure activities. Purpose of this study is to determine the effects of RNT in postural deformities among academicians and non-academician in higher learning institution. Methods: Sample size estimated as 100 male and female patients were selected, they will be randomly selected based on posture evaluation and work based on desk job and lecturing (academician & non academician). The inclusion criteria were as follows: (1) age between 30–50 years; and (2) willing and able to give informed consent for participation in the study. All participants were free from spinal pain and had no previous injury or surgery in the spine and abdominal regions. Discussion: This randomized controlled trial assessed the effectiveness of Reactive Neuromuscular Training (RNT) on craniovertebral angle (CVA) and shoulder angle (SA) among higher learning institution populations, including academicians and non-academicians. Significant improvements in CVA were observed for both groups after 12 weeks of RNT, with academicians increasing from 45.60° to 52.20° (p < 0.001) and non-academicians from 45.31° to 50.13° (p < 0.001). The control group showed some improvements in SA, but the RNT group demonstrated a notable reduction in neck disability, as indicated by the Neck Disability Index (NDI), with scores decreasing from 6.46 to 5.04 for academicians (p = 0.022) and from 6.44 to 4.88 for non-academicians (p = 0.005). These findings suggest that RNT effectively enhances postural alignment and reduces neck disability in workplace settings. Conclusion: This study demonstrated that Reactive Neuromuscular Training (RNT) effectively improves Forward Head Posture (FHP) among tertiary institution populations, including academic and non-academic professionals. Participants receiving RNT showed marked improvements in craniovertebral angle (CVA), enhancing neuromuscular control and postural alignment. Minimal differences in improvement between groups indicate a positive response to RNT, especially among sedentary academics. These findings suggest the integration of RNT into workplace wellness programs to address postural issues and reduce musculoskeletal disorder risks. Limitations include a short intervention period and reliance on CVA as the sole FHP measure, highlighting the need for further research on the long-term effects and additional postural assessments.